Level of Knowledge and Attitude of Senior High School 1 Sidrap Teenagers Regarding the Selection and Usage of Facial Whitening Cream Cosmetics - Aulia Ryanda; Ismail Ibrahim; Ida Adhayanti (Media Publikasi Cendekia Indonesia, 2023)
Beauty is often associated with having an ideal shape, white and glowing skin, white teeth, and a pleasant voice. Smooth skin is a crucial factor in one's appearance, reflecting their identity. This encourages individuals, especially teenage girls, to aspire to achieve flawless skin. One cosmetic product frequently used by teenagers in Indonesia is the whitening cream, commonly referred to as bleaching cream. The emergence of facial whitening products in the market is driven by consumer demand, aligning with the current trend among teenagers who seek fair skin, thus impacting teenagers' pursuit of perfection. The objective of this study was to assess the level of knowledge and attitudes among adolescents at SMAN 1 Sidrap regarding the selection and use of facial whitening cream cosmetics. Respondents were selected using a cross-sectional design method, aiming to determine the knowledge and attitudes of adolescents at SMAN 1 Sidrap. The results indicate that the knowledge level is in the low category (35.68%), while the attitudes fall into the very good category (20.03%). The Chi-Square test yielded a p-value of 0.325, revealing no significant relationship between the level of knowledge and attitudes of SMAN 1 Sidrap adolescents toward the selection and use of facial whitening cream cosmetics.